PENGARUH RASIO KEUANGAN TERHADAP KONDISI FINANCIAL DISTRESS - Darmiyanti, Agustina; Widati, Listyorini Wahyu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Financial distress is a picture of the financial condition of a company that was not healthy before going bankrupt. One way to detect financial distress is to analyze using financial ratios. This study aims to examine the effect of financial ratios such as leverage, profitability, liquidity and operating cash flow in manufacturing companies listed on the Indonesia Stock Exchange in 2018 to 2020. The sampling technique used in this study was the purposive sampling method. obtained as many as 495 samples of companies. The result of this research is that profitability has a negative effect on financial distress. Meanwhile, leverage, liquidity and operating cash flow have no effect on financial distress..